2002
DOI: 10.1081/cnv-120001150
|View full text |Cite
|
Sign up to set email alerts
|

Cancer/Testis Antigens: Structural and Immunobiological Properties

Abstract: Characterization of tumor-associated antigens recognized by cytotoxic T lymphocytes which has evolved during recent years opens new possibilities for specific anti-cancer immunotherapy. Among different groups of tumor-associated antigens, cancer/testis (CT) antigens (expressed in many tumors and among normal tissues only in testes) represent the most perspective antigens for immunotherapy because of their broad tumor-specific expression. More than 50 CT antigens have been described so far and, for many of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 87 publications
1
57
0
1
Order By: Relevance
“…3 In vitro and in vivo experiments have demonstrated that some CT antigens, for example, NY-ESO-1, are capable of provoking potent T-cellmediated immunity to directly kill tumor cells and release cytokines to interfere with the growth of tumor cells, and stimulated antibody response. 12,13 Promising results have been observed in clinical trials using peptide vaccines derived from CT antigens for tumor immunotherapy. 14,15 HCC is the third highest cause of cancer death worldwide with a global incidence of 1.2 million new cases per year.…”
Section: Discussionmentioning
confidence: 99%
“…3 In vitro and in vivo experiments have demonstrated that some CT antigens, for example, NY-ESO-1, are capable of provoking potent T-cellmediated immunity to directly kill tumor cells and release cytokines to interfere with the growth of tumor cells, and stimulated antibody response. 12,13 Promising results have been observed in clinical trials using peptide vaccines derived from CT antigens for tumor immunotherapy. 14,15 HCC is the third highest cause of cancer death worldwide with a global incidence of 1.2 million new cases per year.…”
Section: Discussionmentioning
confidence: 99%
“…For the restricted expression, CTAs are considered as candidate targets of cancer vaccines (26,27). Immunization against BORIS was shown to be effective in treating mice injected with BORIS-expressing cancer cells (28,29).…”
Section: Ctcfmentioning
confidence: 99%
“…The 'cancer-testis' (CT) antigens are a unique class of antigens that demonstrate high levels of expression in adult male germ cells, but generally not in other normal adult tissues, and aberrant expression in a variable proportion of a wide range of different cancer types (10)(11)(12). This fact makes CT antigens especially attractive targets for specific immunotherapy.…”
Section: Introductionmentioning
confidence: 99%